(untitled) (Global Journal of Management and Business Research, 2021)
The survival and profitability of any company depends on the ability of this company to meet the needs of its customer satisfactorily. Thus, the perception of customer about the services offered by the company and their satisfaction becomes a crucial tool for business managers. The main objective of this paper is to investigate the effect the effect of customers’ satisfaction on profit of the mobile telecommunication sector in Bamenda Municipality. A sample of 105 respondents was constituted using random sampling technique. The Multiple Correspondence Analysis was used to construct indexes of profit, customer expectation, perceived quality and perceived value and the Ordinary Least Squares estimation technique was used to test the hypotheses of the study.